New approach to book cipher: web pages as a cryptographic key - Mammadov, Farman Khubali (Національний технічний університет "Харківський політехнічний інститут", 2023)
New approach to book cipher: web pages as a cryptographic keyResearch relevance: Since ancient times, people have widely used methods of concealment and coding during information sharing, and ensuring the protection of information is currently relevant. Encryption methods are developing daily in order to ensure the reliable protection of confidential information and the exchange of data on the network. The subject and purpose of the research are to develop an encryption method, which is based on the ideology of book cipher and uses web pages as a cryptographic key, in the organization of a secure exchange of information. The following tasks are solved in the article: The article provides information about book cipher and analyzes modern methods of book cipher, as well as proposes a novel encryption method involving the use of web pages as a cryptographic key. Research methods: In the paper methods of analysis and synthesis are used. Obtained results and conclusions: The possibility of transforming the book cipher is proved, and a novel encryption method involving the use of web pages as a cryptographic key is proposed. The article also provides a comparison between the proposed encryption method involving the use of Internet pages as a cryptographic key with the classic book cipher method.

Актуальність дослідження: З давніх часів люди широко використовували методи приховування та кодування під час обміну інформацією, і забезпечення захисту інформації є актуальним в даний час. Методи шифрування щодня розвиваються, щоб забезпечити надійний захист конфіденційної інформації та обмін даними в мережі. Предметом і метою дослідження є розробка методу шифрування, який базується на ідеології книжкового шифру та використовує веб-сторінки як криптографічний ключ, для організації безпечного обміну інформацією. У статті вирішуються наступні завдання: y статті наводиться інформація про книжковий шифр та аналізуються сучасні методи книжкового шифрування, а також пропонується новий метод шифрування з використанням веб-сторінок як криптографічного ключа. Методи дослідження: У роботі використовуються методи аналізу та синтезу. Отримані результати та висновки: доведено можливість трансформації книжкового шифру та запропоновано новий метод шифрування з використанням веб-сторінок як криптографічного ключа. У статті також проведено порівняннязапропонованого методу шифрування з використанням інтернет-сторінок як криптографічного ключа з класичним методом книжкового шифру.
Новий підхід до книжкового шифру: веб-сторінки як криптографічний ключ
Keywords: cryptography; symmetric encryption; encryption algorithms; book cipher; cryptographic key; web pages; криптографія; симетричне шифрування; алгоритми шифрування; книжковий шифр; криптографічний ключ; веб-сторінки